2017
DOI: 10.15448/1980-6108.2017.1.25389
|View full text |Cite
|
Sign up to set email alerts
|

Congenital toxoplasmosis: perception of knowledge and primary prevention measures among healthcare professionals and pregnant women treated in public healthcare facilities

Abstract: Aims:To evaluate knowledge about toxoplasmosis among pregnant women and healthcare professionals and to evaluate the knowledge acquired by pregnant women after health education actions. Methods: Five hundred pregnant women and 141 healthcare professionals from health units in Niterói, state of Rio de Janeiro, answered a questionnaire, received information about toxoplasmosis and had access to an interactive educational model and to folders between 2013 and 2016. After 3 months, 145 pregnant women answered the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
1
14
0
7
Order By: Relevance
“…A previous study conducted in Brazil on 405 pregnant women, aimed at knowing the factors associated with better knowledge of toxoplasmosis, showed that the percentage of pregnant women reporting better knowledge of protozoan disease increased with the age, the education level and the pregnancy number [36]. The same results were observed, in a study conducted in 2017 by the same author, on 500 pregnant women in Niteroi, State of Rio de Janeiro [21]. Recent research, conducted on 440 female students in Saudi Arabia by Mahfouz et al .…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A previous study conducted in Brazil on 405 pregnant women, aimed at knowing the factors associated with better knowledge of toxoplasmosis, showed that the percentage of pregnant women reporting better knowledge of protozoan disease increased with the age, the education level and the pregnancy number [36]. The same results were observed, in a study conducted in 2017 by the same author, on 500 pregnant women in Niteroi, State of Rio de Janeiro [21]. Recent research, conducted on 440 female students in Saudi Arabia by Mahfouz et al .…”
Section: Discussionsupporting
confidence: 58%
“…In particular, from the experience of two studies conducted previously [21, 22], a questionnaire ad hoc was developed. A pre-testing conducted on a random sample allowed the optimisation of the instrument and to determine the time needed to complete the questionnaire too.…”
Section: Methodsmentioning
confidence: 99%
“…Com o estudo foi evidenciado a necessidade de reforçar todos os meios de contaminação, além de evidenciar a necessidade de capacitação dos profissionais e de fomentar a educação em saúde das mulheres gestantes e comunidade de maneira geral. Moura et al, (2017) em uma amostra de 500 gestantes teve como resultado que apenas 19% destas tiveram orientações do profissional médico ou enfermeiro sobre a toxoplasmose, enquanto 45,2% referem que 'ouviram falar' sobre a doença por conhecidos e amigos mas contam com informações insuficientes sobre os meios de contaminação, tratamento e possíveis complicações. Moura et al, (2016) entrevistou 405 gestantes entre os anos de 2013 e 2015 e mostrou que 57,3% das entrevistadas desconheciam qualquer informação sobre a doença, ou apenas relacionavam a 'doença do gato' sem maiores informações.…”
Section: -Fontes Aa 2019unclassified
“…O objetivo da profilaxia secundária é a utilização de métodos de detecção da toxoplasmose, por meio de triagem sorológica, para identificar e tratar infecção aguda durante a gravidez e reduzir a transmissão materno-fetal e suas consequentes sequelas de longo prazo para a criança. A prevenção terciária consiste na detecção intrauterina da infecção pelo T. gondii, por diagnóstico neonatal, e a administração do tratamento o quanto antes possível para redução da severidade das sequelas (MOURA et al, 2017).…”
Section: Introductionunclassified
“…O consenso geral entre pesquisadores é representado pelo fato de a educação em saúde ser a estratégia mais eficaz para prevenir a toxoplasmose, reduzindo os riscos de exposição da gestante à infecção e suas sequelas fetais. A ampla e repetida divulgação impressa e falada dos fatores de risco, assim como a participação de todos os profissionais de saúde e pacientes, é essencial para a eficiência de programas preventivos e de acompanhamento a longo prazo, de maneira contínua, envolvendo inclusive mudanças de hábitos de vida da população (BRASIL 2012a;MILLAR et al, 2014;SILVA et al, 2014;LEHMANN, SANTOS & SCAINI, 2016;MOURA et al, 2016;WALCHER, COMPARSI & PEDROSO, 2016;MOURA et al, 2017;MOURA et al, 2019;OLIVEIRA et al, 2019;ROSTAMI et al, 2019;SOUSA et al, 2019;TELESSAÚDE, 2019;BENITEZ et al, 2020;ROSTAMI et al, 2020;SAMPAIO et al, 2020).…”
unclassified